A Multi-Session Evaluation of a Haptic Device in Normal and Critical Conditions: a Mars Analog Mission - Julie Manon; Jean Vanderdonckt; Michael Saint-Guillain; Vladimir Pletser; Cyril Wain; Jean Jacobs; Audrey Comein; Sirga Drouet; Julien Meert; Ignacio Sanchez Casla; Olivier Cartiaux; Olivier Cornu (International Journal of Interactive Multimedia and Artificial Intelligence)
While visual interaction is typically evaluated as an instantaneous, one-shot activity that considers only a snapshot of factors, haptic interaction is more challenging to evaluate as it involves a continuous touch process evolving over time. To better understand how to evaluate haptic interaction, this paper performs a multisession evaluation of a haptic device to be used by astronauts in future lunar and Mars missions, based on eight factors. Three groups of two members (𝑛 = 6 ) applied, either as operator or assistant, a newly developed external fixator (EZExFix) to fix a fracture of the tibial shaft. Astronauts had different levels of expertise, i.e., in anatomy, mechanical engineering, and without, and participated in eight timed runs. Among these eight matches, four sessions were conducted with different time frames and compared to a stress test, a reproduction of the experiment in very stressful conditions, and a session simulating critical conditions in an extra-vehicular activity.